Cyberloafing Review of Psychological Capital and Conscientiousness on Pidie District Health Service Employees - Intan Rizki Karlinda; Farida Agus Setiawati (Eduvest - Journal of Universal Studies, 2025)
Technological advances and the Internet transform the way humans interact, learn, work, and access information. Cyberloafing is one of the emerging phenomena, where employees use internet access during working hours for personal activities. Many factors influence cyberloafing, including psychological capital (PsyCap) and conscientiousness. Research uses a quantitative approach to the type of correlational research. The research was conducted at one of the health departments. Sampling uses probability sampling, where every individual in the population has an equal chance to be selected as a sample. In this study, data collection techniques use online questionnaires or Google Forms distributed to respondents as a selected tool. In this study using descriptive data analysis techniques, the subsequent test pre- conditional analysis precedes the normality and multicolinerity test, and finally the double regression analysis. The results of categorization in the field showed that high levels of psychological capital correlated with lower rates of cyberloafing in the workplace. Field data showed differences from previous predictions, where both levels of cybersecurity and conscientiousness both had a picture of very low categories. Analysis shows that cyberloafing is affected by both variables by 48%. As for the advice to the agency is to organize a training program aimed at improving the psycap and conscientiousness of employees. The effort to develop the psychcap and consciousness can be seen as a strategic investment in strengthening the well-being and productivity of employees, in addition to effectively reducing the likelihood of cyberloafing behavior.